Employee readiness for information sharing in computer-based occupational health and wellbeing management - Fernando, M.; Fidge, C.; Sahama, T. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Employee readiness to share personal information is crucial for the uptake of e-Health systems in occupational health and well-being. We investigated employee health data sharing preferences using a mixed methods sequential research approach. Through a review of the literature and thematic analysis of data from focus group discussions with 26 employees, we identified six information categories for overall health and well-being of employees and five different parties who may share employee healthrelated information. We then identified relationships between those parties and health and well-being information categories, using a correspondence and cluster analysis of data from a single-stage questionnaire survey with 360 respondents. We showed that employees are ready to share information on work-related emotional health and their work environment with employers, physical health with doctors and insurers, healthy behaviours with close friends, and basic access and overall satisfaction with family members.
Keywords: Health and well-being, Personal Health Records (PHR), employer-sponsored personal, health records (ESPHR), occupational health